Crop rotation. VI. Assessment of wheat yield by observing a two years rotation period - Santos, Henrique Pereira dos; Pereira, Luiz Ricardo; Lhamby, Júlio Cesar B.; Reis, Erlei Melo (Pesquisa Agropecuaria Brasileira, 2014)
During a six-year period at EMBRAPA/Centro Nacional de Pesquisa de Trigo (CNPT), at Passo Fundo, RS. Brazil, the effect of two cropping systems was assessed in relation to wheat production: one including wheat (Triticum aestivum L.), oats (Avena sativa L.) and flax (Linum usitatissimum L.) and other one with wheat, lupine (Lupinus albus L.) and rapeseed (Brassica napus L.). The experiment followed a rotational schedule in which wheat returned to the same plot at intervals of three years. The treatments were arranjed in a randomized completed block design, with four replications and plots having 120 m2. Winter crops were set by convencional drilling and soybeans by direct drilling. It was concluded that the highest wheat yields was obtained when wheat was seeded after lupins and rapeseed, and that two winters of rotation may stabilize wheat yields.